2021
DOI: 10.1088/1742-6596/2145/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

Newton’s law of cooling experiment set using Arduino temperature sensor

Abstract: The research aims to develop the experimental set of the temperature measurement in liquid by Arduino program displaying data on a smartphone via the Blynk application. The experimental set is composed of 1) 2 liquid temperature sensors (DS18B20 model), 2) Arduino program, and 3) LED screen for showing the temperature value in unit of °C and connect to a smartphone. The Arduino temperature sensor 1 and sensor 2 of the experimental set have 0.57% and 0.51% errors, respectively, compared with the temperature sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…11 is an expression of Newton's law of heating, while Eq. 22 implies Newton's law of cooling (Bastos et al, 2022;Chanthamanee et al, 2022;Galeriu, 2018).…”
Section: Model For the Increment And Decrement Of Water Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…11 is an expression of Newton's law of heating, while Eq. 22 implies Newton's law of cooling (Bastos et al, 2022;Chanthamanee et al, 2022;Galeriu, 2018).…”
Section: Model For the Increment And Decrement Of Water Temperaturementioning
confidence: 99%
“…This condition causes the rate of heat flow to decrease. When the temperature of the water is the same as the temperature of the container wall, there is no more heat flowing from the wall to the water so that the rise in water temperature will stop (Chanthamanee et al, 2022;Will et al, 2017). There is no longer an increase in water temperature.…”
Section: Figure 5 Comparison Of the Pattern Of Water Temperature-chan...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main parts are nine digital input/output pins, one analog input pin, a USB connection, the power jack, and a reset button. The NodeMCU V3 ESP8266 can be programmed with the Arduino Software (IDE) and powered by an AC to DC adapter (or battery) to start [9]. NodeMCU V3 ESP8266 in this research is shown in Figure 1A.…”
Section: Nodemcu V3 Esp8266mentioning
confidence: 99%